2021
DOI: 10.1158/0008-5472.can-21-0052
|View full text |Cite
|
Sign up to set email alerts
|

PPARα Agonist Fenofibrate Enhances Cancer Vaccine Efficacy

Abstract: Reducing metabolic stress within the tumor microenvironment (TME) could be essential for improving the efficacy of cancer immunotherapy. Using a mouse model of melanoma, we show here that appropriately timed treatment with the PPARα agonist fenofibrate improves the ability of a T cell–inducing cancer vaccine to delay tumor progression. Fenofibrate reduced the use of glucose by tumor and stromal cells in the TME and promoted the use of fatty acids for their metabolic needs. The glucose within the TME was in tur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…A previous study reported that fenofibrate inhibited proliferation and induced apoptosis in Ishikawa endometrial cancer cells [ 49 ]. Moreover, it promotes metabolism of fatty acids over glucose for the metabolic needs in tumor microenvironment thus decreasing tumor progression [ 50 ]. In order to explore the therapeutic potential of fenofibrate, we started a preliminary validation through molecular docking, which can predict binding affinities between molecule and protein residues using binding free energy (ΔGbind) [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that fenofibrate inhibited proliferation and induced apoptosis in Ishikawa endometrial cancer cells [ 49 ]. Moreover, it promotes metabolism of fatty acids over glucose for the metabolic needs in tumor microenvironment thus decreasing tumor progression [ 50 ]. In order to explore the therapeutic potential of fenofibrate, we started a preliminary validation through molecular docking, which can predict binding affinities between molecule and protein residues using binding free energy (ΔGbind) [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, this study is one of the first that describes the correlation between the expression of nuclear receptors (in particular PPARγ) and peritumoral inflammation or TIL levels in relation to prognosis in BC. Although some studies exist on PPARα in melanoma [ 62 , 63 , 64 ], PPARγ has, to our knowledge, never been investigated in relation to TILs and survival in any form of cancer. In our whole cohort of sporadic breast cancers, PPARγ expression in the cytoplasm of cancer cells was positively correlated with TIL levels and peritumoral inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study discovered that in MC38-OT I cancer model, the tumor microenvironment produces immunological defective tumor-infiltrating DCs (TIDCs), which can suppress dendritic cells' anti-tumor regulatory function, and this impact is produced by PPARα activation [48]; however, an exciting study indicated that the PPARα agonist Fenofibrate could boost the ability of a T-cell-inducing melanoma vaccine to delay tumor progression [49], which appears to contradict the finding above. These findings suggested that PPARα plays a significant role in hematologic malignancies.…”
Section: Chronic Lymphocytic Leukemia (Cll)mentioning
confidence: 95%